Transformational Da'wah Leadership Model of Persatuan Islam (Persis) Organization in Facing Global Challenges - Zaenudin, Jeje; Fauzan, Pepen Irpan; Rustandi, Ridwan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
This study analyzes the transformational da'wah leadership model of Persatuan Islam during the 2022-2027 period when the organization entered its first century. Using the constructivism paradigm and a qualitative approach through the case study method, this study investigates the mainstreaming of Persis da'wah in terms of discourse, movement, and activity, especially those reflected in the leadership vision and jihad program of the Central Leadership for the 2022-2024 period. Data was collected through in-depth interviews with Persis leaders, participatory observation, and document analysis, which were then analyzed using thematic analysis techniques. The study results show that transforming the Persis paradigm from "explaining Islam" to "presenting Islam" requires a progressive and contextual da'wah leadership model. This transformational leadership model must integrate Islamic values with the demands of the times, provide solutions to contemporary community problems, and build a sustainable da'wah ecosystem. Through this approach, Persis can maintain its relevance as a da'wah institution and contribute significantly to the development of Islamic civilization, which is rahmatan lil 'alamin.